The Role of Self Assessment as Moderating Variable in the Effect of Risk Management and Leverage on Financial Performance - Widiasmara, Anny; Paramitha Devi, Heidy; Violita, Cindy (KnE Social Sciences, 2024)
The impact of the COVID-19 pandemic caused significant problems in the banking industry’s profit and loss report which showed a decline of 18.565 billion which occurred in 2020. At the beginning of 2019, the profit and loss statement of banking companies was 34.478 billion but now at the end of 2020, the profit and loss statement of banking companies is 15.913 billion (Indonesian Banking Statistics - July 2021, 2021). The purpose of this study was to determine the role of self-assessment as a moderating variable in the influence of risk management and leverage on financial performance. This research was conducted in banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique in this study used purposive sampling. The research method used is a quantitative approach using multiple regression analysis and moderate regression analysis (MRA) using the SPSS version 25 program. The results of this study are credit risk (NPL), leverage (DER), and hurt financial performance (ROA); liquidity risk (LDR) does not affect financial performance (ROA), self-assessment can moderate the influence of credit risk (NPL), liquidity risk (LDR) and leverage (DER) on financial performance (ROA). The researcher hopes that this research can provide implications and support for the development of accounting science, especially in the field of financial accounting related to risk management and leverage. Keywords: credit risk (NPL), liquidity risk (LDR), leverage (DER), financial performance (ROA)